Construction of Environmental Roads in Padang Cermin Village in the Development of Langkat Regency Area - Rudi Kataren; Abdi Sugiarto; Cut Nuraini (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the existing conditions of environmental roads before development, assess the impact of development on community mobility and economic activities, and identify supporting factors, inhibitions, and sustainability strategies for road construction in Padang Cermin Village, Lalat Regency. The method used is a descriptive qualitative approach, with data collection through field observations, interviews with the community and village officials, and documentation. The results of the study show that before construction, the condition of the environmental roads in Padang Cermin Village was still in the form of dirt and was heavily damaged, thus hampering the mobility of residents and economic activities. After development, there was a significant increase in accessibility, a decrease in transportation costs, an increase in the number of MSMEs, and an increase in community participation in economic activities. The construction of environmental roads plays an important role in supporting the development of the Langkat Regency area, especially in accelerating local economic growth and strengthening inter-regional connectivity. Key supporting factors include government support, community participation, and institutional collaboration. The recommended sustainability strategies are improving the quality of infrastructure, periodic maintenance, community empowerment, and integration of development with regional economic development plans. Thus, the construction of environmental roads in Padang Cermin Village has been proven to provide significant economic, social, and spatial benefits for the sustainable development of the Langkat Regency area.